Kwame Nkrumah's contribution to Pan-Africanism : an Afrocentric analysis - Poe, D. Zizwe (Daryl Zizwe), 1954- (African studies (Routledge (Firm)), 2003)
Analyses contributions made by Kwame Nkrumah (1909-1972) to the development of the Pan-African agency from the 1945 Pan-African Congress in Manchester to the military coup d'etat of Nkrumah's government in February 1966.